2020
DOI: 10.1111/pce.13817
|View full text |Cite
|
Sign up to set email alerts
|

Volatiles from the fungal phytopathogen Penicillium aurantiogriseum modulate root metabolism and architecture through proteome resetting

Abstract: Volatile compounds (VCs) emitted by the fungal phytopathogen Penicillium aurantiogriseum promote root growth and developmental changes in Arabidopsis. Here we characterised the metabolic and molecular responses of roots to fungal volatiles. Proteomic analyses revealed that these compounds reduce the levels of aquaporins, the iron carrier IRT1 and apoplastic peroxidases. Fungal VCs also increased the levels of enzymes involved in the production of mevalonate (MVA)‐derived isoprenoids, nitrogen assimilation and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 22 publications
(24 citation statements)
references
References 105 publications
(157 reference statements)
0
24
0
Order By: Relevance
“…( Badri et al, 2013b ; Schulz-Bohm et al, 2017 ; Sasse et al, 2018 ; Huang et al, 2019 ). Air application of microbial VCs enhances root growth ( Gutiérrez-Luna et al, 2010 ; Ditengou et al, 2015 ; García-Gómez et al, 2019 ) and ethylene production ( García-Gómez et al, 2020 ), and promotes changes in root exudate composition ( Hernández-Calderón et al, 2018 ). Recent studies have shown that ethylene emitted by roots can control the rhizosphere microbial community assembly, indicating that this volatile hormone can be used by plants as a cue to interact with soil microorganisms ( Chen et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…( Badri et al, 2013b ; Schulz-Bohm et al, 2017 ; Sasse et al, 2018 ; Huang et al, 2019 ). Air application of microbial VCs enhances root growth ( Gutiérrez-Luna et al, 2010 ; Ditengou et al, 2015 ; García-Gómez et al, 2019 ) and ethylene production ( García-Gómez et al, 2020 ), and promotes changes in root exudate composition ( Hernández-Calderón et al, 2018 ). Recent studies have shown that ethylene emitted by roots can control the rhizosphere microbial community assembly, indicating that this volatile hormone can be used by plants as a cue to interact with soil microorganisms ( Chen et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…VCs emitted by beneficial microorganisms promote growth and developmental changes, enhance photosynthesis, improve nutrient acquisition, elicit plant defenses and inhibit the growth of plant pathogens when applied via the air ( Ryu et al, 2003 ; Chaurasia et al, 2005 ; Kai et al, 2007 ; Zhang et al, 2008 , 2009 ; Gutiérrez-Luna et al, 2010 ; Kottb et al, 2015 ; Garnica-Vergara et al, 2016 ; Sánchez-López et al, 2016 ; Guo et al, 2020 ). Recent studies have shown that this capacity also extends to VCs emitted by phytopathogens and microorganisms that do not normally interact mutualistically with plants ( Ezquer et al, 2010 ; Bitas et al, 2015 ; Sánchez-López et al, 2016 ; Cordovez et al, 2017 ; Li et al, 2018 ; García-Gómez et al, 2019 , 2020 ; Moisan et al, 2019 ), although several lines of evidence indicate that the mechanisms involved in some plants’ responses to VCs emitted by beneficial and pathogenic microorganisms are different ( Hernández-Calderón et al, 2018 ; García-Gómez et al, 2020 ). In Arabidopsis , enhanced growth and photosynthesis promoted by air application of fungal VCs is associated with increases in levels of active forms of cytokinins (CKs), photosynthetic pigments and transitory starch in leaves, together with reductions in abscisic acid (ABA) contents, and changes in the transcriptome and proteome through mechanisms involving signaling of redox-activated photosynthesis and long-distance communication between roots and the aerial part of the plant ( Zhang et al, 2008 ; Sánchez-López et al, 2016 ; Ameztoy et al, 2019 , 2021 ; García-Gómez et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…In WT leaves, reduction of the expression of proteins of the Clp protease system (e.g., ClpP5, ClpP6, ClpR3, and ClpT2) promoted by small fungal VCs was associated with down-regulation of ClpP5, ClpP6, and ClpR3 transcript levels and enhanced levels of CPN60A1, CPN60B1, CPN60B2, CPN60B3, CPN20, CPN10-1, and CPN10-2 and their encoding transcripts. No such increases in the expression of plastidial chaperonins and co-chaperonins occurred in leaves of cfbp1 plants or in roots of WT plants exposed to small fungal VCs (García-Gómez et al, 2020). This indicates that, as illustrated in Figure 7, plastid proteome adaptation to fungal VCs in leaves involves photosynthesisdriven chloroplast-to-nucleus retrograde signaling mechanisms wherein transcriptional up-regulation of plastidial chaperones and down-regulation of the Clp protease system play important roles.…”
Section: Plant Responses To Small Fungal Vcs Involve Chloroplast-to-nmentioning
confidence: 93%
“…They downregulated the expression of the iron-regulated transporter 1 (IRT1) and upregulated the expression of enzymes involved in the ethylene synthesis pathway. Furthermore, fungal volatile compounds downregulated the expression of invertases and aquaporin genes, cumulatively leading to a reduction of the turgor and consequently to root elongation [108]. The same authors found that Arabidopsis plants exposed to the volatiles emitted by P. aurantiogriseum displayed enhanced tolerance to drought stress [108], emphasizing the importance of these naturally produced compounds to the improvement plant growth under various environmental challenges.…”
Section: Volatile Emission By Phytopathogenic Organisms Represents a ...mentioning
confidence: 99%
“…The latter initiate a cumulative change in the expression of genes involved in various metabolic processes [26]. Recently, García-Gómez et al [108] provided evidence that the volatile compounds produced by P. aurantiogriseum modify root metabolism and architecture under both normal and drought conditions, resulting in improved nutrient and water use efficiency in Arabidopsis. In that study, a comprehensive metabolic, proteomic, and transcriptomic approach was undertaken to evaluate which regulatory networks were associated with the positive effects of the volatile compounds on root development.…”
Section: Volatile Emission By Phytopathogenic Organisms Represents a ...mentioning
confidence: 99%